Crisis, Ideology, and Interventionist Policy Ratchets. (November 2019) - Bjørnskov, Christian; Rode, Martin
Proper government reaction to economic crisis has long been a central element of public policy debate and is experiencing a revival after the Great Recession of 2008. Previous studies argue on theoretical and empirical grounds that crises may lead to more interventionist policies, but also cause deregulation and liberalization. This article claims that policy responses will partly depend on the core economic ideology of government, causing ideologically heterogeneous post-crisis strategies. Employing a panel of 69 countries for which salient ideology measures can be constructed, we find that growth crises between 1975 and 2015 caused larger increases in government size and regulatory policy when countries have left-wing governments. We also find some evidence of policy ratchets, meaning that certain crisis policies present a tendency to become permanent, regardless of the ideology of successive governments in power. Rolling back the public sector in size and scope seems to be possible, but our results show that, on average, it does not clearly occur as an ideologically driven reaction to anti-crisis policies.